Benznidazole therapy for Chagas disease in asymptomatic Trypanosoma cruzi -seropositive former blood donors: evaluation of the efficacy of different treatment regimens - André Pires Antunes; Antônio Luiz Pinho Ribeiro; Ester Cerdeira Sabino; Marise Fagundes Silveira; Cláudia Di Lorenzo Oliveira; Ana Cristina de Carvalho Botelho (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract: INTRODUCTION: Chagas disease currently affects 5.7 million people in Latin America and is emerging in non-endemic countries. There is no consensus concerning the efficacy of trypanocidal therapy for patients with the chronic form of the disease. We evaluated cardiac function and sociodemographic, clinical, and serologic characteristics of a group of asymptomatic Trypanosoma cruzi-seropositive former blood donors, and compared the effects of benznidazole treatment applied for different lengths of time. METHODS: Blood donors who screened positive for T. cruzi between 1998 and 2002 were recruited 10 years later for follow-up (n = 244); 46 individuals had received treatment. Three subjects had terminated treatment prematurely. The remaining 43 individuals were divided into two groups: individuals who had received benznidazole therapy for 50-60 days (n = 28; BT ≤60 group) or more than 60 days (n = 15; BT >60). Serologic assays, biochemical tests, electrocardiographic, echocardiographic, and clinical examinations were performed on all participants. Parasite loads were determined by qualitative and quantitative polymerase chain reaction. RESULTS: Parasitemia was significantly reduced in the BT ≤60 and BT >60 groups compared with the untreated group. There were no differences in epidemiologic profiles or clinical, biochemical, electrocardiographic, or echocardiographic data between any of the groups. CONCLUSIONS: Despite elimination or significant reduction in parasitemia in patients with chronic Chagas disease who received benznidazole, there was no clinical difference between those who were treated for >60 days and those treated for a shorter duration. Furthermore, the adverse effects of benznidazole appear to be less severe than previous reports would suggest.